GASTRIC ULCEROGENICITY OF FENOPRON ANTAGONIZED BY PARACETAMOL IN ALBINO RATS - Draz, Umar; Janjua, M. Zahoor (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: The ulcerogenic effect of fenopron and its protection by paracetamol was observed under dissecting as well as laboratory microscope. The protection was complete under dissecting microscope, in the dose of 250 mg/kg. body weight but there was significant decrease in erosion score with gum acacia followed by Fenopron. Mucosal thickness was significantly increased in paracetamol followed by fenopron group as compared to other group. Increased secretory activity of mucous neck cells was observed in the same group which might have resulted as protection of rat stomach by the damaging effect of fenopron; due to increased production of mucous as well as prostaglandin.